Inside Cover: A novel in vivo Cerenkov luminescence image‐guided surgery on primary and metastatic colorectal cancer (J. Biophotonics 3/2020). Issue 3 (5th March 2020) - Zhang, Zeyu; Qu, Yawei; Cao, Yu; Shi, Xiaojing; Guo, Hongbo; Zhang, Xiaojun; Zheng, Sheng; Liu, Haifeng; Hu, Zhenhua; Tian, Jie
Abstract: This study presents a novel intraoperative in vivo imaging approach which harnessed Cerenkov luminescence (CL) to detect primary and metastatic colorectal cancer (CRC) using clinically approved radiopharmaceuticals. In the mice and swine experiments, the proposed approach effectively improved the effect of CRC surgery. The approach is believed to be promising for utilizing CL in open surgery. Further details can be found in the article by Zeyu Zhang, Yawei Qu, Yu Cao et al. (e201960152 ) Abstract : This study presents a novel intraoperative in vivo imaging approach which harnessed Cerenkov luminescence (CL) to detect primary and metastatic colorectal cancer (CRC) using clinically approved radiopharmaceuticals. In the mice and swine experiments, the proposed approach effectively improved the effect of CRC surgery. The approach is believed to be promising for utilizing CL in open surgery. Further details can be found in the article by Zeyu Zhang, Yawei Qu, Yu Cao et al. (e201960152 )